(untitled) (Experimental biology, 2015)
Comparative analysis of distribution and number of common rats were made in the Kyrgyz Republic for 2005 and 2010 years. Settlements of common rats increased in 2010 as compared with 2005 in Bishkek city and Tchu oblast.Intense settling of common rats was in 2005 in the south of the Republic and a noticeable decrease of the rodent is observed in 2010. In 2005 innumerability of common rats is noticed in the south of Kyrgyzstan, more exactly, in Jalalabat and Batken oblasts. For five years it was decreased two times and common rats became usual for inhabitants. Later settling of common rats occurred in Talas and Issyk Kul oblasts. New human settlements are occupied by common rats and increasing in number is discovered in the whole Republic, except Naryn oblast..